2012
DOI: 10.1007/978-3-642-35740-4_29
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient GPU Implementation for Variational Optic Flow Based on the Euler-Lagrange Framework

Abstract: The Euler-Lagrange (EL) framework is the most widely-used strategy for solving variational optic flow methods. We present the first approach that solves the EL equations of state-of-the-art methods on sequences with 640 × 480 pixels in near-realtime on GPUs. This performance is achieved by combining two ideas: (i) We extend the recently proposed Fast Explicit Diffusion (FED) scheme to optic flow, and additionally embed it into a coarse-to-fine strategy. (ii) We parallelise our complete algorithm on a GPU, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…By means of 2-D optic flow computations, it has already been demonstrated that FED is very well-suited for parallelisation on GPUs [13]. In this subsection, we illustrate that this also holds for Fast-Jacobi and in three dimensions.…”
Section: Higher Dimensional Problems and Gpu Implementationssupporting
confidence: 56%
See 1 more Smart Citation
“…By means of 2-D optic flow computations, it has already been demonstrated that FED is very well-suited for parallelisation on GPUs [13]. In this subsection, we illustrate that this also holds for Fast-Jacobi and in three dimensions.…”
Section: Higher Dimensional Problems and Gpu Implementationssupporting
confidence: 56%
“…for optic flow computation with a parallel GPU implementation [13], fast filtering methods on smartphones [14], medical image analysis [15,16], variational depth-from-defocus [17], and a cyclic projected gradient method for convex optimisation [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the parallel treatment of the pixels within video frames, exploiting the large number of computing units in GPUs. We note also that we obtain reduced acceleration when processing low resolution 8 …”
Section: Performancementioning
confidence: 80%
“…Authors in [7] presented the CUDA implementation of the Horn-Shunck optical flow, that offered a real-time processing of 316×252 video resolution. Gwosdek et al [8] developed a GPU implementation of the Euler-Lagrange (EL) framework for solving variational optical flow methods using sequences with 640x480 pixels in near-real-time.…”
Section: Related Workmentioning
confidence: 99%
“…Another approach is to consider the solution of the Euler-Lagrange equation as the steady state of the corresponding diffusion process (34), and use the Fast Explicit Diffusion (FED) principle [105] to accelerate convergence by adapting the time steps. The implementation of [107] exploits the natural parallelization of explicit schemes to achieve a quasi real-time version of the variational method of [286] on GPU, based on FED.…”
Section: Continuous Methodsmentioning
confidence: 99%